PENGARUH METODE PEMBELAJARAN COMPLETE CENTENCE DALAM PEMBELAJARAN MENULIS TEKS ULASAN SISWA - Nanalia, Nanalia; Missriani, Missriani; Agustina, Juaidah (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
The purpose of this study was to investigate whether the complete sentence learning method affects students' ability to write reviews. The research method used was the pretest-posttest control group design experimental method. The population consists of students in Class VIII of SMP Negeri 16 Palembang, which consists of two classes. The data collection method is the test method: pre-test and post-test. A computational investigation of the t-test yielded tcount = 29.95 and ttable = 1.67 for a table with a significance level of 0.05±n, so tcount > ttable and the alternative hypothesis or Ha is accepted. Keywords: complete centence, ability to write review text